Anxiety and Depression in Egyptian Patients with Acne Vulgaris - Nora N. Hussien; Afaf M. Eladl (Journal of High Institute of Public Health, 2021)
Background: Acne vulgaris is a prevalent skin condition that may affect the perception of body image and adversely affect social and psychological states. This disease has been associated with rates of depression, anxiety, failure to thrive at school and in social environments, suicidal ideation, and suicidal attempts that are higher than in individuals without this disease. Objective: To estimate the frequency of anxiety and depression in patients with acne vulgaris and determine the association between acne severity and anxiety and depression in those patients Methods: A comparative cross-sectional study was conducted in Zagazig University Hospital on 92 subjects (46 patients with acne and 46 individuals without acne); they were interviewed. The researcher used the Global Acne Grading System (GAGS) to classify acne and the Hospital Anxiety and Depression Scale (HADS) to determine anxiety and depression. Results: In the acne group, 23.9% had anxiety and 13.1% had depression. In the control group, 6.5% had anxiety and 4.3% had depression; the difference was statistically significant. Of the acne group patients with severe acne, 66.7% had anxiety and 44.4% had depression. There was a significant correlation between the severity of acne evaluated by GAGS and HADS for anxiety (r = 0.712, p < 0.001) and GAGS and HADS for depression (r = 0.584, p < 0.001). Conclusion: Acne vulgaris may be associated with depression and anxiety, with a linear relationship between its severity and the presence of depression and anxiety. Patients with acne vulgaris should undergo a continually psychiatric evaluation by their primary care physician to avoid the negative effects on their mental and social health.